Notes on a Postcolonial Musicology: Kofi Agawu and the Critique of Cultural Difference [Agawu, Kofi. 2003. Representing African Music: Postcolonial Notes, Queries, Positions. New York and London: Routledge, 304 pp.] - Scherzinger, Martin (Current Musicology, 2003)
Kofi Agawu’s new book Representing African Music: Postcolonial Notes, Queries, Positions stands in a consciously awkward relationship to traditional ethno-graphic writing on music. Ethnomusicological discourse is characterized by a carefully plotted regimen of priorities, which tends to conduct inquiry away from Western-style music analysis towards anthropological models.